Yield and validation of the scanner for use in the estimation of number of sunflower grains - Souza, E. P.; Fachi, L. R.; Santos, P. R. J.; Savelli, R. A.; Nied, A. H. (Scientific Electronic Archives, 2018)
The commercial exploitation of sunflower is based on the extraction of oil from the achenes and the bran produced, being one of the most important oil supplying species in the world. The objective of the work was to verify the yield of grains from commercial crops in the sunflower and to validate the method of using the scanner for the seed count. The data were collected in two commercial crops, located in the municipalities of Diamantino-MT and Campo Novo dos Parecis-MT. The variables were evaluated between January and July 2014: grain yield, grain yield components and plant height. The seed count was done manually and through an HP Photosmart C4480 All-in-One Scanner scanner, and the images were processed to estimate the number of seeds per chapter in the Quant.v program. 1.0.2. Grain yield data were correlated with grain yield components. The mass of achenes per chapter showed a significant correlation with grain yield. In order to calibrate the digitized images, 1190 and 1107 seeds in the agrobel and aguara varieties, respectively, are adequate, and the seed counting method with the digitizer is accurate and can replace the manual method, in addition, it allows to work with larger samples of achenes per chapter with less time spent.